Chinese discourses on happiness - Wielander, Gerda; Hird, Derek (Hong Kong University Press, 2018)
Happiness is on China's agenda. From Xi Jinping's ""Chinese Dream"" to online chat forums, the conspicuous references to happiness are hard to miss. This groundbreaking volume analyzes how different social groups make use of the concept and shows how closely official discourses on happiness are intertwined with popular sentiments. The Chinese Communist Party's attempts to define happiness and well-being around family-focused Han Chinese cultural traditions clearly strike a chord with the wider population. The collection highlights the links connecting the ideologies promoted by the government